EVALUASI KETERLAMBATAN PROYEK PEMBANGUNAN GEDUNG AKIBAT MANAJEMEN DAN PRODUKSI DENGAN METODE EVAS - Desfita, Mediana; Chairi, Maiyozzi; Asraf, Muhammad Bahrul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Delays that occur on a project can delay time and cause cost losses. Delays in construction are said to be the completion of construction within meeting the work time targets exceeding those agreed upon by all parties. This research aims to determine the performance of building project work based on the results of management work delay analysis, evaluate the results of work delay analysis due to production on project work, and find out what factors are obstacles in project work. One method of controlling project costs and time is the evaluation variance at schedule method or what is usually called the EVAS method using the Microsoft Project application. Based on the evaluation results, data obtained on the duration of project work that had been carried out reached the 6th week, to be precise, 42 days, experiencing a setback of 1 day of work, for preliminary work, the duration of work was obtained with a status of 14 days